Anatomy of a Forgery: An Agathokles Cu-Ni Double Unit - Taylor , Lloyd W. H. (KOINON: The International Journal of Classical Numismatic Studies, 2024)
The Bactrian Indo-Greek Rulers (BIGR) research tool has facilitated the identification of an example in commerce of a cast forgery of a Cu-Ni coin of the Baktrian king Agathokles. This identification was made by the matching coin to its visually identical double in a museum collection in the BIGR database. In all likelihood the museum coin is also a fake, one that had its origins in the mid-19th century.